The Reflection of Lithuania in Hungarian Digital Media in 2022–2024 in the Light of the Recent European Security Situation - Šarūnas Rinkevičius (Politologija)
The paper analyses the representation of Lithuania in the five most visited Hungarian news websites (Index, Telex, Portfolio, 24, 444) in the period from 1 January 2022 to 30 June 2024 aiming to evaluate in which thematic contexts and in what ways Lithuania is being represented in the Hungarian language media in the light of the recent European security situation. The study revealed that the Hungarian news websites analysed in the research covered various issues related to Lithuania providing a broad panoramic view on topicalities of Lithuania. These news were divided into two parts: the security news, covering anything related to Russia‘s war against Ukraine and European security issues, and also all the other news. The study revealed that Lithuania during the researched period was mainly represented in the light of the Russian war against Ukraine and the European security situation, yet there were also many other regularly appearing references to Lithuania in the Hungarian media reflecting Liethuanian topicalities. The study aims to contribute to the discussions about the bilateral Lithuanian and Hungarian relations in the twenty first century also aspiring to focus on the European integration dimension in the media in the light of unity within NATO and EU.